Study on Simulation of the Yields of Radionuclide 68Ge Based on FLUKA Monte Carlo Code - Zhe WANG; Shizhong AN; Yunlong ZHAO; Fei WANG; Guoying GUAN; Lu LU; Sumin WEI; Luyu JI; Tianjian BIAN (Journal of Isotopes)
With the development of nuclear science and technology，the application of PET medical radionuclides is increasing，and the demand is increasing. But the Ge-Ga generators used to provide 68Ga medical radionuclide are all dependent on imports. In order to carry out the research of Ge-Ga generator technology，we will carry out the pilot experiments of 68Ge production.In the study，the simulated production of medical radionuclide 68Ge based on FLUKA Monte Carlo program. The end of bombardment (EOB) yields of 68Ge with 100 μA，200 μA and 500 μA beam intensity were calculated by 14 MeV，30 MeV and 70 MeV proton beams irradiating Ga targets enriched with 69Ga for 1 hour，12 hours and 24 hours，respectively. The changes of EOB yields and the activity of radionuclides on the targets were analyzed. After 24 hours irradiation by 30 MeV/500 μA proton beam，the EOB yield of 68Ge nuclide is 3.13×1010 Bq，which is similar to the EOB yield with 24 hours irradiation by 70 MeV/500 μA proton beam，which is 4.54×1010 Bq. There are fewer radioactive impurities on the target and higher input and output benefit with 30 MeV proton beams. Therefore，the proton energy for 68Ge nuclide production is 30 MeV. The research could provide some theoretical basis and support for 68Ge production pilot experiment and mass production.